2017
DOI: 10.1007/s10040-017-1651-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping fracture flow paths with a nanoscale zero-valent iron tracer test and a flowmeter test

Abstract: The detection of preferential flow paths and the characterization of their hydraulic properties are important for the development of hydrogeological conceptual models in fractured-rock aquifers. In this study, nanoscale zerovalent iron (nZVI) particles were used as tracers to characterize fracture connectivity between two boreholes in fractured rock. A magnet array was installed vertically in the observation well to attract arriving nZVI particles and identify the location of the incoming tracer. Heat-pulse fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Improved tomograms can be achieved by increasing the source-receiver density, by optimal and full usage of information of measured data, instead of, for example, utilizing the trends and characteristics of response data only, and by combining different measurements that deliver complementary data. The combined use of salt tracer and electrical resistivity tomography [17], of salt tracer and ground penetrating radar [41], as well as of nanoscale zero-valent iron tracer and flowmeter testing [42] have been proposed for better delineation of fracture flow paths. However, combining different methods also raises efforts and the cost of field investigation campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Improved tomograms can be achieved by increasing the source-receiver density, by optimal and full usage of information of measured data, instead of, for example, utilizing the trends and characteristics of response data only, and by combining different measurements that deliver complementary data. The combined use of salt tracer and electrical resistivity tomography [17], of salt tracer and ground penetrating radar [41], as well as of nanoscale zero-valent iron tracer and flowmeter testing [42] have been proposed for better delineation of fracture flow paths. However, combining different methods also raises efforts and the cost of field investigation campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Gong and Rossen [16] focused on the influence of fracture aperture distribution, and found that even a well-connected fracture network could behave like a much sparser network when the aperture distribution was broad enough. Chuang et al [17] used nanoscale zero-valent iron (nZVI) particles as tracers to characterize fracture connectivity between two boreholes in fractured rock. The position where the maximum weight of attracted nZVI particles was observed coincides with the depth of a permeable fracture zone delineated by the heat-pulse flowmeter.…”
Section: Introductionmentioning
confidence: 99%